O controle jurisdicional das multas tributárias - Aleluia, Erick Calheiros (2022)
This work focuses on the judicial control of legality and constitutionality of disproportionate and confiscatory tax fines, since the normative system prohibits the Judiciary from reducing or limiting these penalties to a specific percentage. The problem covers the relationship between the republican principle, the tripartition of powers and the limits of competences of the bodies that produce sanctions, confronting the varied positions defended in the doctrine and the position taken by the Federal Supreme Court on the subject